The Influence of Financial Literacy on The Investment Behavior of Indonesian Migrant Workers in Japan - Puput Rohmawati; Sintesa, Nika (Pandawan, 2024)
This study aims to analyze the influence of financial literacy on the investment behavior of Indonesian migrant workers in Japan, taking into account factors such as age, education level, and income. The research focuses on 50 Indonesian migrant workers in the Miyazaki area of Japan. Financial literacy is considered a key factor that can affect investment behavior, helping these workers make better investment decisions. A quantitative approach was employed, using descriptive statistical methods and correlation analysis based on questionnaire data that measured respondents' understanding of financial literacy and its impact on their investment behavior. The results show that financial literacy has a positive and significant effect on investment behavior. Higher levels of financial literacy are associated with improved investment decisions. Additionally, age, education, and income also have a significant impact. These findings highlight the importance of developing more effective financial literacy education and training programs for Indonesian migrant workers in Japan, as improved financial literacy can lead to better investment decisions, increased access to investment opportunities, and enhanced financial well-being.